Social Mobility and the Importance of Networks: Evidence for Britain - Oscar Marcenaro Gutierrez; John Micklewright; Anna Vignoles (Institute for the Study of Labor (IZA), 2014)
Greater levels of social mobility are widely seen as desirable on grounds of both equity and efficiency. Debate on social mobility in Britain and elsewhere has recently focused on specific factors that might hinder social mobility, including the role of internships and similar employment opportunities that parents can sometimes secure for their children. We address the help that parents give their children in the job market using data from the new age 42 wave of the 1970 British Cohort Study. We consider help given to people from all family backgrounds and not just to graduates and those in higher level occupations who have tended to be the focus in the debate in Britain. Specifically, our data measure whether respondents had ever had help to get a job from (i) parents and (ii) other relatives and friends and the form of that help. We first assess the extent and type of help. We then determine whether people from higher socio-economic status families are more or less likely to have such help and whether the help is associated with higher wages and higher occupations. Our paper provides insight into whether the strong link between parental socio-economic background and the individual's own economic success can be explained in part by the parents assisting their children to get jobs. We find parental help to have a strong social gradient. But we are unable to identify a clear link between any particular type of help advice, help through contacts etc. and individuals' wages or occupations.
Keywords: J62; 330; social mobility; networks; family; wages